VD_FINDINFO HC / 2017 / 257 vom 14. März 2017 - VD Tribunal cantonal (2017)
EXPULSION DE LOCATAIRE, PROCÉDURE DE CONCILIATION, LITISPENDANCE | 257d CO, 200 CPC (CH), 59 al. 2 let. d CPC (CH), 41 CDPJ, 1 al. 3 LJB